Physical, antimicrobial and antioxidant properties of starch‐based film containing ethanolic propolis extract. (7th July 2015) - de Araújo, Grace Kelly P.; de Souza, Silvio J.; da Silva, Marcos V.; Yamashita, Fabio; Gonçalves, Odinei H.; Leimann, Fernanda V.; Shirai, Marianne A.
Summary Propolis is a natural product that meets the requirements as functional additive for food packaging due to its antioxidant and antimicrobial activities. In this work, ethanolic propolis extract (EPE) was incorporated in cassava starch films, and characterisations with respect to their microstructure, mechanical properties, water vapour permeability (WVP), moisture sorption kinetics as well as antimicrobial and antioxidant capacities were performed. The results showed that tensile strength was not affected (P > 0.05) by the presence of EPE but Young's modulus decreased about 50% when compared to control films possibly because of EPE plasticiser effect. When 1% EPE was used, changes in moisture sorption properties were detected by a slightly hydrophobic character at films WVP. When extracted from the films, propolis retained its antioxidant activity. The films exhibited antimicrobial activity against Staphylococcus aureus and Escherichia coli even at low EPE concentrations (0.5%) mainly due to its phenolic compounds.